Encontros com crianças e imagens cinematográficas: a expansão dos movimentos de invenções curriculares - Lovatte, Geiza Turial de Almeida (2024)
This research explores the strength of encounters between children and cinematographic images within the school context. Its main objective is to map the curricular movements that emerge from these encounters. Specifically, it aims to trace the intensities of these encounters and the children’s fabulations; to problematize the processes of curricular deterritorialization and reterritorialization; and to present the educational product, the scrapescritos, created from these encounters with short films. The theoretical framework draws on the philosophy of Gilles Deleuze and Félix Guattari, whose approach provides a conceptual structure for experiencing learning and curriculum in a non-linear and inventive way. The research evokes Deleuze’s approach to affect and percept, emphasizing these elements in the experience and using cinematographic images as thought triggers. Methodologically, it employs the cartographic method, which seeks to follow processes and investigate productions, focusing on trajectories rather than representing a fixed object. The use of conversational networks is proposed as spaces for collective knowledge production, experimenting with the rhizomatic curriculum as an alternative to the traditional curriculum. The research suggests that the knowledge, actions, and affects that emerge from children’s encounters with cinematographic images enable a break with dogmatic thinking. In this movement, children create new images of curriculum, learning, school, and the world. The results indicate that cinematographic images are forces capable of creating new possibilities, expanding the power of the collective, and affirming a life that does not fit within standardized curricula.